Roles for the FCRL6 Immunoreceptor in Tumor Immunology - Davis, Randall S. (Frontiers in Immunology, 2020)
Members of the Fc receptor-like (FCRL1–6) gene family encode transmembrane glycoproteins that are preferentially expressed by B cells and generally repress responses via cytoplasmic tyrosine-based regulation. Given their distribution and function, there is a growing appreciation for their roles in lymphoproliferative disorders and as immunotherapeutic targets. In contrast to FCRL1–5, FCRL6 is distinctly expressed outside the B lineage by cytotoxic T and NK lymphocytes. Its restricted expression by these orchestrators of cell-mediated immunity, along with its inhibitory properties and extracellular interactions with MHCII/HLA-DR, represent a newly appreciated axis with relevance in tolerance and cancer defense. The significance of FCRL6 in this arena has been recently demonstrated by its upregulation in HLA-DR+ tumor samples from melanoma, breast, and lung cancer patients who relapsed following PD-1 blockade. These findings imply a potential mechanistic role for FCRL6 in adaptive evasion to immune checkpoint therapy. Here we review these new developments in the FCRL field and identify new evidence for the prognostic significance of FCRL6 in malignancies that collectively indicate its potential as a biomarker and therapeutic target.